MiR-381-abundant small extracellular vesicles derived from kartogenin-preconditioned mesenchymal stem cells promote chondrogenesis of MSCs by targeting TAOK1. (February 2020) - Jing, Hui; Zhang, Xiaoyang; Luo, Kai; Luo, Qiancheng; Yin, Meng; Wang, Wei; Zhu, Zhongqun; Zheng, Jinghao; He, Xiaomin
Abstract: Small extracellular vesicles (sEVs) derived from mesenchymal stem cells have been shown to possess potent regenerative potential. In this study, we evaluated the chondrogenic effect of sEVs derived from kartogenin-preconditioned human umbilical cord mesenchymal stem cells (hUCMSCs). sEVs were isolated from the supernatants of KGN-preconditioned hUCMSCs (KGN-sEV) by gradient ultra-centrifugation, and internalized by native hUCMSCs, thereby inducing the chondrogenic differentiation. The underlying mechanism of KGN-sEV-induced chondrogenesis was explored by high-throughput sequencing and verified by transfection with the corresponding mimic and inhibitor. Sequencing identified the unique enrichment of a set of miRNAs in KGN-sEV compared with sEVs derived from unpreconditioned cells (un-sEV). Overexpression/inhibition in vitro and in vivo demonstrated that this chondrogenesis-inducing potential was primarily attributed to miR-381-3p, one of the most abundant miRNAs in KGN-sEV. Dual-luciferase reporter assays showed that miR-381-3p promoted chondrogenesis through direct suppression of TAOK1 by targeting its 3' untranslated region, thereby suppressing the Hippo signaling pathway. Collectively, our results highlight the regenerative potential of KGN-sEV to induce chondrogenic differentiation of MSCs, which is mainly achieved by delivering sEV-miR-381-3p, which targets TAOK1.